1999
DOI: 10.1093/humrep/14.7.1690
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant L-arginine treatment for in-vitro fertilization in poor responder patients

Abstract: The objective of the present study was prospectively and randomly to evaluate the role of L-arginine in improving uterine and follicular Doppler flow and in improving ovarian response to gonadotrophin in poor responder women. A total of 34 patients undergoing assisted reproduction was divided in two groups according to different ovarian stimulation protocols: (i) flare-up gonadotrophin-releasing hormone analogue (GnRHa) plus elevated pure follicle stimulating hormone (pFSH) (n = 17); and (ii) flare-up GnRHa pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 58 publications
0
45
0
9
Order By: Relevance
“…Various factors, including aging and previous ovarian surgery, which mainly reflect early depletion of ovarian reserves, have been associated with a poor response; however, mechanisms other than a deficiency in ovarian function can be involved in poor responses, such as alterations in intraovarian factors or gonadotropin receptor regulation [2]. A poor response to ovulation stimulation results in high cancellation rates of up to 76% and extremely low pregnancy rates from 3.2-14% [3][4][5][6][7][8]. Various strategies for poor responders, including flare regimens and agonist and traditional antagonist protocols have been attempted; however, at present, there is no definitive evidence that poor outcomes can be reversed by a specific protocol [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors, including aging and previous ovarian surgery, which mainly reflect early depletion of ovarian reserves, have been associated with a poor response; however, mechanisms other than a deficiency in ovarian function can be involved in poor responses, such as alterations in intraovarian factors or gonadotropin receptor regulation [2]. A poor response to ovulation stimulation results in high cancellation rates of up to 76% and extremely low pregnancy rates from 3.2-14% [3][4][5][6][7][8]. Various strategies for poor responders, including flare regimens and agonist and traditional antagonist protocols have been attempted; however, at present, there is no definitive evidence that poor outcomes can be reversed by a specific protocol [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the above functions, NO may be directly involved in the physiology of reproductive organs. The NO participates in periovulatory modulation of ovarian blood flow (4)(5)(6) and seems to be involved in follicular maturation and ovulation (1,7). However, although the NO local synthesis within the uterus may be important for regulating endometrial, cervical, and myometrial activity (8), its role in embryonic implantation has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide has vasodilation properties that improve blood circulation and flow in the sex organs, resulting in oocyte development and embryo implantation. 13 In conclusion, our study showed that both the increased protein intake and the proportion of energy obtained from protein were associated with an increased risk of infertility.…”
Section: Discussionmentioning
confidence: 58%